Mandatory Spending in Indonesian Constitution - adhika wicaksana ardiansyah (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2023)
Mandatory spending in the constitution is a constitutional practice in realizing the concept of a Welfare State. Mandatory spending in the Indonesian constitution begins with the 4th amendment to the 1945 Constitution. What is the meaning of mandatory spending formulation in constitution and what is its relation to State Finances is a problem that will be answered in this research. This aims to find out the meaning of the mandatory spending formulation, and its relationship to State Finances. Through a normative juridical research approach, answers to the above problems will be sought through available legal materials. This research conclude that ensuring budget allocation from certain sectors was the motivation for including mandatory spending. The mandatory spending formula gains legitimacy because of the need for government support in certain sectors (in this research it is the education sector). The formulation of mandatory spending is related to the state budget system and is a globally recognized practice. Another conclusion from this research is that there is no conflict between mandatory spending in the Indonesian constitution and State Finance. The potential for disharmony in the formulation of mandatory spending from a State Finance perspective will emerge in regulations under the constitution.